Equipment development and research for more performance and safety - Senner, V.; Lehner, S.; Böhm, H. (Science and Skiing IV, 2009)
INTRODUCTION: Alpine skiing and snowboarding are among the most popular sports and due to the good economic development in Eastern Europe and in Asia the worldwide number of active skiers (approx. 70 Million) is still increasing. Skiing and snowboarding however are not without risk and epidemiology ranks them in the group of those leisure time sports with increased probability to suffer an injury. Current injury statistics of different countries correspond fairly well and register between 405 and 355 MDBI (mean days between injuries) in skiing (Endres et al., 2007 and Laporte et al., 2007). For snowboarding the rate is one injury for every 358 to 216 days of riding (Endres et a., 2007 and Greenwald et al., 2000). Sport equipment engineering tries to contribute to more safety in these sports i.e. by improving the ski binding's release behavior, by optimizing the boot-binding interface towards better force transmission, by designing equipment which is easier to handle in different situations and last but not least - by working on improved protection gear. In most cases the major problem with such developments is not the design process itself. Most effort needs to be put into the evaluation process that is essential to quantify the effects of the new solution. Thus the development of adequate models, measuring devices and inquiring methods are the biggest concerns for sport technology research. The presentation will mainly focus on this task, showing various approaches and the possibilities hereof for the optimization of ski and snowboarding equipment.